Academic Tendencies and Inner Tone in Assessment of Works of Shukur Khalmirzayev - Sayyora Khalmirzayeva (International Journal of Scientific Trends, 2024)
A systematic analysis of the life and work of one of the most important representatives of twentieth-century Uzbekistani literature, awarded the title of “national writer”. It examines his contributions to various prose genres, including novel, short story, essay, drama and journalism. It is noted that Shukur Khalmirzayev established a new school in the genre of storytelling in Uzbek national literature. He was recognized as a rare talent after a thorough analysis and study of the stages of the writer’s development, as well as his contributions to national and world literature.